Probing disease-related proteins with fluorogenic composite materials. (4th December 2014) - He, Xiao-Peng; Zang, Yi; James, Tony D.; Li, Jia; Chen, Guo-Rong
Abstract : We summarise the development and application of fluorogenic composite materials (FCMs) based on graphene oxide (GO), carbon nanotubes (CNTs) and gold nanoparticles (AuNPs) for detection of disease related proteins on both the molecular and cellular levels. Abstract : Construction of composite materials based on the self-assembly of fluorescently labeled biomolecules with a variety of micro- or nano-quenching materials (by the Förster Resonance Energy Transfer mechanism) for the fluorogenic recognition of disease-related proteins has become a dynamic research topic in the field of fluorescence recognition. Here we summarize the recent progress on the composition of fluorescence dye-labeled biomolecules including sugars, peptides and nucleotides with organic (graphene and carbon nanotubes) and inorganic (gold nanoparticles) materials. Their application in the fluorescence detection of proteins and enzymes on both the molecular and cellular levels is discussed. Perspectives are proposed with respect to the future directions of employing these composite materials in the recognition of pathological proteins.